(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The nursing profession plays a critical role in healthcare systems globally, blending scientific knowledge with compassionate care. This article explores the multidimensional nature of nursing, including its historical development, educational frameworks, clinical responsibilities, and evolving role in interdisciplinary healthcare. Special emphasis is placed on the scientific foundations of nursing practice, current challenges, and the future directions shaped by technology, policy, and global health trends.